FourFold Asthma Study (FAST): a study protocol for a randomised controlled trial evaluating the clinical cost-effectiveness of temporarily quadrupling the dose of inhaled steroid to prevent asthma exacerbations. Issue 1 (December 2016) - Skeggs, Andrew; McKeever, Tricia; Duley, Lelia; Mitchell, Eleanor; Bradshaw, Lucy; Mortimer, Kevin; Walker, Samantha; Parrott, Steve; Wilson, Andrew; Pavord, Ian; Brightling, Chris; Thomas, Mike; et al.
Abstract Background Asthma is one of the commonest chronic diseases in the UK. Acute exacerbations of asthma are unpredictable, disruptive and frightening. They cause considerable morbidity and account for a large component of the health service costs of asthma. The widespread use of an asthma self-management plan, designed to encourage disease monitoring and timely intervention, can reduce exacerbations and is, therefore, recommended for all patients with asthma. Unfortunately, the majority of patients are not provided with such a plan. There are a variety of reasons for this but uncertainty about what to include in the plan when asthma control is deteriorating, but before the need for orally administered corticosteroids, is a contributing factor. The aim of this trial is to determine whether an asthma self-management plan, which includes a temporary quadrupling of the dose of inhaled corticosteroid when asthma control starts to deteriorate, reduces asthma exacerbations requiring orally administered corticosteroids or unscheduled health care consultation for asthma. Methods A multicentre, pragmatic, randomised trial in adults aged over 16 years with a clinical diagnosis of asthma, treated with a licensed dose of inhaled corticosteroid and at least one exacerbation in the previous 12 months requiring treatment with systemic corticosteroids. Participants will be randomised to either a self-management plan, which includes a temporary (maximum of 14 days) fourfold increase in inhaled corticosteroid or the same plan without an increase in inhaled corticosteroid. Participants will be followed up at 6 and 12 months and will attend the clinic for an additional visit if their asthma control deteriorates. The primary outcome is time to first asthma exacerbation, defined as the need for systemic corticosteroids and/or unscheduled health care consultation for asthma. The estimated sample size is 1800 participants. Discussion The FAST trial is an independent study that has been prioritised and commissioned by the National Institute for Health Research (NIHR) in the United Kingdom. It will provide high-quality evidence to inform clinical decision-making on the role of an asthma self-management plan, which includes a temporary fourfold increase of inhaled corticosteroid, when asthma control starts to deteriorate. The first participant was randomised on 17th May 2013 and recruitment will close on 31 January 2016 with the last patient last visit taking place in January 2017. Trial registration ISRCTN: 15441965, registered on 25 April 2013.